Manufacturing processes for design professionals - Thompson, Rob (Thames & Hudson, 2007)
Today's product designers are presented with a myriad of choices when creating their work and preparing it for manufacture. They have to be knowledgeable about a vast repertoire of processes, ranging from what used to be known as traditional "crafts" to the latest technology, to enable their designs to be manufactured effectively and efficiently. Information on the internet about such processes is often unreliable, and search engines do not usefully organize material for designers